Derivative securities pricing and modelling - Batten, Jonathan; Wagner, Niklas F. 1969- (Emerald, 2012)
This edited volume will highlight recent research in derivatives modelling and markets in a post-crisis world across a number of dimensions or themes. The book addresses the following main areas: derivatives models & pricing, model application & performance backtesting, new products & market features. Particular themes encompass: - continuous and discrete time modeling, - statistical arbitrage models, - arbitrage-free pricing, risk-neutral implied densities, - equilibrium pricing approaches (including e.g. co-integration), - applications of methods in computational statistics including simulation, - computationally intense techniques for pricing, estimation and backtesting, - complex derivative products, - credit and counterparty risk, - innovative market and product structures.
Includes index.